The behaviour of both Listeria monocytogenes and rat ciliated ependymal cells is altered during their co-culture. - Mina J Fadaee-Shohada; Robert A Hirst; Andrew Rutman; Ian S Roberts; Chris O'Callaghan; Peter W Andrew (PLoS ONE)
Background Ciliated ependymal cells line the cerebral ventricles and aqueducts separating the infected CSF from the brain parenchyma in meningitis. Principal findings Investigation of the interaction of Listeria monocytogenes with cultured rat brain ependymal cells showed that certain strains reduced the beat frequency of the cilia but all the strains studied significantly reduced the ciliary beat amplitude (the linear distance travelled by the tip of each cilium per beat cycle). Conclusion The presence of the ependyma caused aggregation of some listeria strains and in some cases extracellular material also was seen in association with bacterial aggregates. These observations were dependent on the expression of genes required for invasion, intracellular survival and listerial cell to cell spread that are regulated by the transcriptional activator, positive regulatory factor A (PrfA).